Implementasi Sales Force Automation untuk Mengoptimalkan Efisiensi Operasional pada Klinik Kecantikan Ellea Liora di Tasikmalaya - Caesar, Calvin; Budi, Akhmad (Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This study aims to develop a web-based Sales Force Automation (SFA) system as a solution for managing customer information and operations at Ellea Liora, a beauty clinic in Tasikmalaya. With the increasing demand for beauty services, the manual system currently in use leads to inefficiencies in transaction recording, appointment scheduling, and customer data management. This research employs a qualitative method with data collection techniques including direct observation, documentation, and literature review to understand system requirements. The system development follows the Rapid Application Development (RAD) methodology to ensure an iterative solution that meets end-user needs. The resulting system features transaction recording, self-service appointment scheduling, electronic invoice generation, inventory management, and structured customer data management. The implementation of this system is expected to enhance Ellea Liora's operational efficiency, accelerate sales processes, reduce human errors, and improve service quality and competitiveness in the beauty industry.